Modeling and analysis of photoconductive detectors based on Hg 1-xCd xTe for free space optical communication - Dwivedi A.D.D.; Chakrabarti P. (My University, 2025)
In this paper we report a theoretical analysis of a long wavelength photoconductive detector for characterizing and optimizing the device in respect of voltage responsivity, quantum efficiency, detectivity and noise equivalent power. The model has been applied to examine the potential of an n-type Hg 0.77Cd 0.23Te photoconductive detector for possible application in free space optical communication system operating at the atmospheric window near 9.6 μ m. In the present analysis we have taken into account all the major recombination mechanisms (e.g., Radiative, Auger, and Shockley-Read-Hall types) including the effect of surface recombination at the interfaces that shape the characteristics of photoconductor. The results obtained on the basis of our analysis reveal that in the absence of surface recombination the device exhibits a peak quantum efficiency of 90%, a maximum detectivity of 10 8 MHz 1/2/W at 77 K, a 3 dB bandwidth of 117.86 MHz and noise voltage of 5.4 × 10 -6 V/Hz 1/2. The sweep-out effect has been found to degrade the detectivity nearly by a factor of 10 at the same temperature and wavelength of operation. The estimated noise equivalent power of the photodetector is of the order of 10 -9 W at 9.6 μm wavelength. © 2007 Springer Science+Business Media, LLC.